Analisis Korelasi Antara Kebiasaan Membaca Dan Kemampuan Membaca Pemahaman Pada Siswa Kelas IX SMP Kemala Bayangkari Makassar - Muhammad Yusuf Yunus; Andri Machmury (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2019)
This study aims to describe whether or not there is a relationship between reading habits and reading comprehension ability in class IX students of SMP Kemala Bayangkari Makassar. This study is a descriptive study using correlational analysis methods. The population in this study was 200 students and the sample was 40 students. In this study data was collected from two sources, namely the questionnaire value from the results of the reading habit questionnaire test and the value of reading comprehension ability from the results of the comprehension reading ability test. Data obtained in the form of primary data using a quantitative descriptive approach with an objective process and analyzing data. The results of the analysis in this study indicate that the relationship between reading habits and reading comprehension ability of class IX students at SMP Kemala Bayangkari Makassar has a positive correlation. In this study, it is hoped that the readers and writers themselves will be able to further improve their reading skills.